Efficiency of botanical extracts from Jatropha curcas L. for the control of Trialeurodes vaporariorum (Hemiptera: Aleyrodidae) - Silva-Illescas, Pedro Fernando (2025)
Introduction. Trialeurodes vaporariorum (Westwood) is considered one of the main pests affecting horticultural and ornamental crops, especially in greenhouses. Effective management of this pest requires the integration of various methods and techniques, including the use of botanical extracts. Objective. To evaluate the efficacy of botanical extracts derived from Jatropha curcas for the control of Trialeurodes vaporariorum under laboratory conditions. Materials and methods. The study was conducted in the Entomology Laboratory of the Crops Protection Research Center, Universidad de Costa Rica. An adaptation of the methodologies described by Liu and Stansly (1995) and Ibrahim and Mostafa (2018) was implemented to evaluate the efficacy, median lethal concentration (LC50), and median lethal time (LT50) of aqueous botanical extracts made from leaves, stems, and seeds of two J. curcas accessions at concentrations of 50, 100, 150, and 200 g/L on T. vaporariorum. Results. The lowest LC50 (1.52 g/L) and LT50 (61.01 hours) values, as well as the highest efficacy values (above 65 %), were achieved with leaf extracts with significant differences observed exclusively in the LT50 values. Concentration was the most important factor in efficacy estimation according to the Akaike information criterion, and efficacy increased by 0.15 % for each concentration unit. None of the evaluated extracts caused phytotoxicity in Solanum melongena L. plants. Conclusions. The leaf extracts are a promising alternative for the control of T. vaporariorum; however, it is necessary to determine the compounds in Jatropha leaves that induce mortality.